Characterization of Unfractionated Heparin: Comparison of Materials from the last 50 Years - Mulloy, Barbara; Gray, Elaine; Barrowcliffe, Trevor W. (Thrombosis and Haemostasis, 2000)
Physicochemical and anticoagulant characteristics of 27 samples from recent batches of commercially produced unfractionated heparin have been determined as part of the process of establishment of the 5th International Standard Unfractionated Heparin. They have been compared with current heparin standards (European Pharmacopoeia, United States Pharmacopoeia, Chinese), with the 4th International Standard Unfractionated Heparin, and with the three predecessor International Standards. The results indicate that the 4th International Standard Unfractionated Heparin, established in 1982, has significantly lower molecular weight and specific activity than recently produced heparin; this is also true of all preceding International Standard Heparins and of the United States Pharmacopoeial standard. The composition of commercial unfractionated heparin may therefore have changed over time; reasons for this are discussed.
Keywords: Unfractionated heparin; molecular weight; NMR spectroscopy; anticoagulant activity; International Standard